Deleuze's philosophical lineage - Jones, Graham (Lecturer in media, communications and writing); Roffe, Jon (Edinburgh University Press, 2009)
Presenting essays by a range of Deleuze scholars and theorists of his work, this book is composed of in-depth analyses of the key figures in Deleuze's lineage, whose significance - as a result of either their obscurity or the complexity of their place in the Deleuzean text - has not previously been well understood. Included are essays on Deleuze's relationship with figures as varied as Marx, Simondon, Wronski, Hegel, Hume, Maimon, Ruyer, Kant, Heidegger, Husserl, Reimann, Leibniz, Bergson, and Freud.